Potential and Feasibility of Mytilus spp. Farming Along a Salinity Gradient - Buer, Anna-Lucia; Maar, Marie; Nepf, Mark; Ritzenhofen, Lukas; Dahlke, Sven; Friedland, René; Krost, Peter; Peine, Florian; Schernewski, Gerald (Frontiers in Marine Science, 2020)
Mussel farming, compared to marine finfish aquaculture, represents an environmentally friendly alternative for a high quality protein source and can at the same time be a measure to remove excess nutrients in eutrophic areas. As such, it is considered as a promising ‘blue growth’ potential and promoted within the European Union. To expand mussel aquaculture, new regions have to be considered because there are multiple marine usages, and spatial limitations occur in coastal areas. The brackish Baltic Sea might be considered for expansion of mussel aquaculture. This study focusses on estimated production potential, economic profitability and nutrient remediation potential of mussel farming at different salinities. Four experimental mussel farms were set up along the German Baltic coast at salinities ranging from 7 to 17 psu. Collected growth data was used to calibrate and validate a Dynamic Energy Budget model and to predict the potential mussel production at twelve sites along the German coast. The estimated production and nutrient removal was used to assess economic profitability, assuming two usages of the harvest: human consumption and mussel meal production. Measured mussel specific growth rates increased with salinity from 0.05 mm d-1 in Greifswald Bay to 0.11 mm d-1 in Kiel Fjord. Within 6 months, a one-hectare farm could produce from 1 t (Darss-Zingst-Bodden-Chain) to 51 t (Flensburg) fresh mussels and remove 1.1 to 27.7 kg P and 24.7 to 612.7 kg N, respectively. Mussel farms at sites west of Rostock at salinities >10 psu could produce 5 cm mussels within 18 months, but only farms at Flensburg, Eckernförde and Kiel Fjord became profitable at a farm size of 4 ha (160,000 m³) at current market prices of 2.2 € kg-1. Regardless of the farm size, none of the farm sites could operate profitable if fresh mussels were sold for animal feeding at sales price of 0.06 € kg-1. Yearly nutrient removal costs at a small-scale farm (1 ha) ranged between 162 € (Flensburg) and 4,018 € (Darss-Zingst-Bodden-Chain) per kg nitrogen, and 3,580 € and 88,750 € per kg phosphorus, respectively.